Analysis of Changes in Body Balance for Women with Multiple Sclerosis - Albertas Skurvydas; Vida Janina Česnaitienė; Kazimieras Pukėnas; Julija Andrejeva; Vytautas Streckis; Dalia Mickevičienė (Lithuanian Sports University, 2018)
Background. To obtain changes in postural control the method of static posturography is usually used. The analysis of posturogram lets us determine the character of these changes, presumes that the body balance complexity, which is expressed in body coordinates of the centre of pressure variation, is less in multiple sclerosis patients than in healthy women. This study aimed at determining the effect of multiple sclerosis on changes in balance control of patients. Methods. Twelve women with multiple sclerosis (mean age - 43.0 ± 5.5 years, body mass index - 24.7 ± 4.2 kg/m 2 ) and 15 healthy women (mean age - 44.5 ± 3.5 years, body mass index - 25.5 ± 2.9 kg/m 2 ) were included in this study. The balance of subjects was assessed applying the method of static posturography. We calculated changes in the coordinates of the centre of body pressure displacement in the lateral and anterior-posterior directions. To assess changes in the displacement of the centre of body pressure in the lateral and anterior-posterior directions two characteristics of advanced signal processing methods, i.e. sample entropy and the index of spectral power dependence on frequency were calculated. Results  and  conclusion.  Traditional  posturogram  analysis  does  not  show  statistically  significant  changes between women with multiple sclerosis and healthy women. The results of the study, applying advanced signal processing methods, have shown that the complexity of the centre of body pressure displacement of women with multiple sclerosis is statistically significantly smaller compared to that of the healthy women studied. This may be a prerequisite for better rehabilitation of stroke control. Keywords: multiple sclerosis, posture control, assesement of posture.